THE CORRELATION BETWEEN BODY COMPOSITION WITH HEART RATE RECOVERY TOWARDS MALE MEDICAL STUDENT IN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Prasetio Kirmawanto; Fitria Nurul Hidayah; Ghifari Sya’bani (Jurnal Ilmiah Hospitality, 2023)
Background: The prevalence of cardiovascular disease and obesity is quite high in Indonesia. Medical students must always be healthy in carrying out the educational process and later, when working as a doctor. Body composition measurements can be used as parameters for early detection of cardiovascular risk. Heart Rate Recovery (HRR) is one of the predictors for mortality associated with the risk of cardiovascular disease. Objective: To determine the correlation between body composition and HRR in male medical study program students. Methods: This study is an analytic correlation study. The subjects were 83 male students. The parameters measured in body composition are body mass index, waist circumference, body fat percentage, and waist-height ratio. The HRR data measured after the Kasch Step Test. The HRR used is HRR 1 minute (HRR1min). The Spearman correlation test used to find a correlation between body composition and HRR. Results: All body compositions were inversely correlated with HRR1min and showed a statistically significant relationship (p <0.05). Waist circumference and body fat percentage are weakly correlated with HRR. Body mass index and waist-height ratio are moderately correlated with HRR. Conclusion: There is a correlation between every aspect of body composition with HRR in male medical students. Components of body composition that are considered to have a significant correlation are body mass index and waist to height ratio